Recursos directamente recaudados y su incidencia en la ejecución presupuestal de la UNAP, periodo 2016 - 2020 - Estrada García, Jesús David (2022)
The purpose of the research work is to analyze the origin of the perception of income and expenses of the RDR, which is appreciated in the budget execution, and then propose policies and guidelines that contribute to the best collection of directly collected resources. The methodology used is a quantitative, descriptive-explanatory approach. The data collection and information gathering technique will be implemented through the MEF transfer portal, as well as a review of specialized bibliography, newspapers and magazines. The research work was developed by obtaining information from the official portal of the Ministry of Economy and Finance where you can have updated and verified data on the National University of the Peruvian Amazon, where the statistical programs for data processing were applied and thus be able to obtain the results of the investigation and its therefore its analysis. According to the analysis methodology, he concluded, the income obtained for the RDR of the National University of the Peruvian Amazon, contributes to the development of institutional plans through the Institutional Operational Plan (POI).